Aspidimorpha (Afroaspidimorpha) rainoni, a new species from Benin (Coleoptera, Chrysomelidae, Cassidinae) - (:unkn) unknown (My University, 2018)
A new species Aspidimorpha rainoni is described from Benin, western Africa. It belongs to the subgenus Afroaspidimorpha Borowiec, 1997 which comrised hitherto 12 species. At first glance the new species is similar to the Aspidimorpha areata (Klug, 1835) widely distributed in Africa but differs in details of dorsal pattern and rounded pronotal corners.
Keywords: African Research